2021
DOI: 10.1007/s44197-021-00013-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Characteristics of Infective Endocarditis at a Cardiac Center in Saudi Arabia

Abstract: Background Infective endocarditis (IE) is a serious disease with complex pathology and significant mortality. Little information is known regarding clinical and microbiological characteristics in Saudi Arabia. This study surveyed these characteristics at a Cardiac Center in Riyadh, Saudi Arabia over a period of 5 years. Methods This retrospective study was done on all infective endocarditis (IE) patients admitted to Prince Sultan Cardiac Center bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 40 publications
5
12
0
1
Order By: Relevance
“…Likewise, studies by Kaasch et al (Kaasch et al, 2014), Lessa et al (Lessa et al, 2010), Gasch et al (Gasch et al, 2013) and others have observed higher incidence of SAB in males than females. In contrast, human females have been suggested to have a somewhat higher mortality rate than males as a result of SAB (Lamagni et al, 2011;Barry et al, 2021). Similarly, Bansal et al (Bansal et al, 2021) and Barry et al recently reported that males have a higher incidence of infective endocarditis (Barry et al, 2021).…”
Section: Biological Sex As a Correlate In S Aureus Infectionmentioning
confidence: 98%
See 1 more Smart Citation
“…Likewise, studies by Kaasch et al (Kaasch et al, 2014), Lessa et al (Lessa et al, 2010), Gasch et al (Gasch et al, 2013) and others have observed higher incidence of SAB in males than females. In contrast, human females have been suggested to have a somewhat higher mortality rate than males as a result of SAB (Lamagni et al, 2011;Barry et al, 2021). Similarly, Bansal et al (Bansal et al, 2021) and Barry et al recently reported that males have a higher incidence of infective endocarditis (Barry et al, 2021).…”
Section: Biological Sex As a Correlate In S Aureus Infectionmentioning
confidence: 98%
“…In contrast, human females have been suggested to have a somewhat higher mortality rate than males as a result of SAB (Lamagni et al, 2011;Barry et al, 2021). Similarly, Bansal et al (Bansal et al, 2021) and Barry et al recently reported that males have a higher incidence of infective endocarditis (Barry et al, 2021). However, this is a common theme of sepsis (Sunden-Cullberg et al, 2020) where sepsis in females is associated with higher mortality, is recognized later and females receive treatment later than males.…”
Section: Biological Sex As a Correlate In S Aureus Infectionmentioning
confidence: 99%
“…Staphylococcus is among the most common causes of endovascular infections, including infective endocarditis (IE), which may occur in the setting of a bloodstream infection [ 12 14 ]. In an experimental aortic valve MRSA IE rabbit model, transthoracic echocardiography was utilized to evaluate the in vivo effect of exebacase on vegetation progression when combined with daptomycin (versus daptomycin alone) [ 8 ].…”
Section: Clinical Relevancementioning
confidence: 99%
“…В развиващите се страни обаче ревматичното сърдечно заболяване остава най-честият предразполагащ рисков фактор за ИЕ [24]. Например метаанализ за Африка, публикуван 2022 г., съобщава за 52% случаи на РСП, Индия -20%, Саудитска Арабия -15%, Латинска Америка -13% [20,[26][27][28]. За сравнение в International Collaboration on Endocarditis -Prospective Cohort Study (ICE-PCS) [2] случаите с РСП са 3%, а по данни на нашия център -2,6%.…”
Section: Risk Factorsunclassified
“…However, in developing countries, rheumatic heart disease remains the most common predisposing risk factor for IE. For example, a meta-analysis for Africa published in 2022 reported 52% cases of RHD, India -19%, Saudi Arabia -15%, Latin America -13% [20,[26][27][28]. In comparison, in the International Collaboration on Endocarditis-Prospective Cohort Study (ICE-PCS) [2] cases of RHD were 3%.…”
Section: Risk Factorsmentioning
confidence: 99%